2018
DOI: 10.1177/1526602818803119
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon Treatment of Femoropopliteal Lesions Typically Excluded From Clinical Trials: 12-Month Findings From the IN.PACT Global Study

Abstract: Purpose: To report a post hoc analysis comparing outcomes between subjects who would have been included in the IN.PACT SFA randomized controlled trial vs those who would have been excluded. Methods: The 1406 subjects enrolled in the IN.PACT Global Study (ClinicalTrials.gov identifier NCT01609296) were retrospectively assigned to a standard-use group (n=281) based on the inclusion and exclusion criteria from the randomized IN.PACT SFA trial; the remaining 1125 patients were assigned to the broader-use group. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Recent data from prospective as well as retrospective registries/studies also demonstrated that DCB angioplasty provides consistent clinical benefit in cohorts of long lesions, 7,29 in-stent restenosis, 8 and other complex lesions. 9,30,31 Although only short-term outcomes (1 and 2 years) are available for these registries/studies; these results provide additional evidence that DCB is a viable treatment option for complex lesion/patient cohorts. Previously, we reported a superior treatment effect of DCB in patients with diabetes mellitus as compared with PTA.…”
Section: Discussionmentioning
confidence: 96%
“…Recent data from prospective as well as retrospective registries/studies also demonstrated that DCB angioplasty provides consistent clinical benefit in cohorts of long lesions, 7,29 in-stent restenosis, 8 and other complex lesions. 9,30,31 Although only short-term outcomes (1 and 2 years) are available for these registries/studies; these results provide additional evidence that DCB is a viable treatment option for complex lesion/patient cohorts. Previously, we reported a superior treatment effect of DCB in patients with diabetes mellitus as compared with PTA.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, 3 DCBs and 2 DES are currently supported by broad and robust evidence, beyond just first-in-human trials, consisting of rigorous, independently adjudicated randomized pivotal trials and large real-world datasets. [1][2][3][4][5][6][7][8][9][10] The most recently released practice guidelines from the Society for Cardiovascular Angiography and Interventions have therefore elected DCB as first line endovascular therapy with the highest level of recommendation (I-A) for a wide array of indications in the femoropopliteal segment. 11 Also noteworthy, several "no-class-effect" claims have been largely and consistently raised pertaining to paclitaxeleluting technologies, specifically based on the multitude of observed technical differences and related outcome variances demonstrated in preclinical and clinical trials.…”
mentioning
confidence: 99%
“…8 Also, the Biolux P-II randomized trial, 9 which compared 36 patients treated with Passeo 18 DCBs and 36 treated with Passeo 18 plain balloons failed to demonstrate any advantage of the DCB. One theory to explain this gap between the BTK territory and the SFA, where improved patency was obtained with DCBs, 20,21 could be explained by the anatomic differences.…”
Section: Discussionmentioning
confidence: 99%
“…One theory to explain this gap between the BTK territory and the SFA, where improved patency was obtained with DCBs, 20,21 could be explained by the anatomic differences. Patients with CLI frequently present more severe lesions that are longer and more calcified compared to claudicants with SFA disease.…”
Section: Discussionmentioning
confidence: 99%